Do you suffer from mitral prolapsed? - Sedigheh Salemi (Iran University of Medical Sciences, 1993)
Prolapsed Mitral Valve Syndrome is a common, benign disorder with prevalence of %0.3-6 in population. This syndrome also is known as Barlows Syndrome and Flaapy Mitral Valve Syndrome. Prolapsed Mitral Valve is the dropping of one or two mitral valve leaflet(s) into the left atrium during ventricular systole. This malformation leads to incomplete closing of mitral valve and regurgitates the blood into atrium. Mitral prolapsed is a result of a kind of abnormal, ongoing leaflet' degeneration